Antithrombotic strategy in patients with atrial fibrillation and acute coronary syndrome. (14th October 2021) - Almeida, I; Santos, H; Santos, M; Miranda, H; Chin, J; Sa, C; Almeida, S; Sousa, C; Almeida, L; ,
Abstract: Background: Atrial fibrillation (AF) is frequent in patients admitted with acute coronary syndromes (ACS). The development of this arrhythmia occurs in 2–21% of patients with non ST-elevation ACS and 21% of ST-elevation ACS. According with the most recent European guidelines, a short period up to 1 week of triple antithrombotic therapy (TAT) is recommended, followed by dual antithrombotic therapy (DAT) using a NOAC and a single antiplatelet agent, preferably clopidogrel. Objective: To compare the antithrombotic strategy (DAT vs TAT) used and its prognostic value in patients with AF and ACS. Methods: Retrospective analysis of patients' data admitted with ACS in a multicentric registry between 10/2010–09/2019. TAT was defined as the prescription of dual antiplatelet therapy and one anticoagulant and DAT as one antiplatelet and one anticoagulant. Survival and rehospitalization were evaluated through Kaplan-Meier curve. Results: 1067 patients were included, mean age 67±14 years, 72.3% male. Patients who developed de novo AF during hospitalization due to ACS were older (75±12 vs 66±14 years, p<0.001) and with higher prevalence of cardiovascular risk factors and cardiovascular disease. AF was more often in patients with ST elevation ACS (53.4%). During hospitalization, AF patients were more often medicated with aspirin, glycoprotein inhibitor, heparin, fondaparinux and vitamin K antagonists. No difference was found regarding P2Y12 inhibitors. AF patients presented more often obstructive coronary disease (normal coronaries 5.4 vs 8.5%, p<0.001) so they were more often submitted to PCI (79.5 vs 70.9%, p<0.001). AF patients presented with higher rates of adverse in-hospital events as re-infarction, heart failure, shock, ventricular arrhythmias, cardiac arrest, stroke, major bleeding and death (p<0.001). At discharge, AF patients were less prescribed with aspirin or ticagrelor, but the rate of clopidogrel prescription was higher, such as vitamin K antagonists or any of the new anticoagulants. In the AF group, 21.5% patients were discharged with TAT and 30.3% with DAT. Concerning patients discharged with TAT, 1-year follow-up revealed no significant differences in mortality (p=0.578), re-admission for cardiovascular causes (p=0.301) and total re-admission rates (p=0.291). Patients discharged with DAT had similar mortality (p=0.623) and re-admission for cardiovascular causes rates (p=0.138), but significant differences were identified regarding total re-admissions (p=0.024). Conclusions: In patients with ACS and de novo AF, a low percentage of patients was discharged with oral anticoagulation (51.8%). In those whose anticoagulation was initiated, DAT was the preferred strategy. 1-year outcomes were not different between the antithrombotic strategy, except for all cause re-admission. Funding Acknowledgement: Type of funding sources: None.